Pengaruh Eco Enzyme Terhadap Radiasi Elektromagnetik Untuk Pemakaian Laptop Dalam Pembelajarn: Pengaruh Eco Enzyme Terhadap Radiasi Elektromagnetik Untuk Pemakaian Laptop Dalam Pembelaran - Hafiz Zulfi; Nyoman Santiyadnya; I Putu Suka Arsa (Universitas Pendidikan Ganesha, 2022)
Electromagnetic radiation generated by laptops can potentially cause health problems for users. The purpose of this research is to limit or suppress the effects of electromagnetic radiation using a multifunctional liquid, namely eco enzyme. The method used is a quantitative - experimental method with a True Experimental research design (Posttest-only control design). There are three treatments, namely using eco enzyme measuring 150 ml, 300 ml, and 500 ml with each distance of 5 cm, 10 cm, 12.5 cm, 15 cm, 20 cm, 25 cm, 30 cm, 32.5 cm, 35 cm, and 40 cm. The results of data analysis were carried out using the Independent Sample T-Test. The laptops that were analyzed in the T-Test were only laptops that had the lowest and highest electromagnetic radiation, namely Acer laptops and Fujitsu laptops. Based on the Independent Sample T-Test, the results showed that there was no effect of eco enzyme to reduce electromagnetic radiation on laptops. Meanwhile, in the 300 ml and 500 ml eco-enzyme, there is an effect of using -enzyme in reducing laptop electromagnetic radiation.